Meaning in Life and Self-Control Buffer Stress in Times of COVID-19: Moderating and Mediating Effects With Regard to Mental Distress - Schnell, Tatjana; Krampe, Henning (Frontiers in Psychiatry, 2020)
Background As evidenced by several studies, mental distress increased substantially during the COVID-19 pandemic. In this period, citizens were asked to exercise a high degree of self-control with regard to personal and social health behavior. At the same time, we witnessed an increase of prosocial acts and shared creative expressions, which are known to serve as sources of meaning. Meaning in life and self-control are acknowledged psychological resources. Especially in times of crisis, meaning in life has been shown to be a crucial factor for resilience and coping. However, threatening and stressful situations can also jeopardize existential security and trigger crises of meaning. The present study aimed to document levels of acute COVID-19 stress and general mental distress in Germany and Austria during the lockdown and in the weeks thereafter. In order to identify potential risk factors related to demographics and living conditions, their associations with COVID-19 stress were analyzed exploratively. The primary objective of the study, however, was to investigate the buffering effect of two psychological resources—meaningfulness and self-control—with regard to the relation between acute COVID-19 stress and general mental distress. Finally, a potential aggravation of mental distress due to the occurrence of crises of meaning was examined. Method A cross-sectional survey was conducted online during lockdown (survey group 1) and the subsequent weeks characterized by eased restrictions (survey group 2). A total of N = 1,538 German-speaking participants completed a questionnaire battery including a novel measure of acute COVID-19 stress, meaningfulness and crisis of meaning (SoMe), self-control (SCS-KD), and a screening of general mental distress, measured by core symptoms of depression and anxiety (PHQ-4). In a first step, associations between living conditions, demographics, and COVID-19 stress were explored. Second, a moderation and a mediation model were tested. Meaningfulness, a measure of presence of meaning in life, as well as self-control were proposed to serve as buffers in a time of crisis, thus moderating the relation between acute COVID-19 stress and general mental distress (double moderation). Crisis of meaning, operationalizing an experienced lack of meaning in life, was proposed to mediate the relationship between acute COVID-19 stress and general mental distress, with an assumed moderation of the association between COVID-19 stress and crisis of meaning by survey group (lockdown versus eased restrictions after lockdown), and a hypothesized moderation of the link between crisis of meaning and general mental distress by self-control (dual moderated mediation). Results COVID-19 stress was slightly right-skewed. Scores were higher during lockdown than in the weeks thereafter. The rate of clinically significant general mental distress was high, exceeding prevalence rates from both the general population and clinical samples of the time before the pandemic. In the weeks following the lockdown (group 2), general mental distress and crisis of meaning were significantly higher than during lockdown (group 1), whereas meaningfulness and self-control were significantly lower. Demographically, age had the strongest association with COVID-19 stress, with older participants perceiving less acute stress (r = −.21). People who were partnered or married suffered less from COVID-19 stress (η2 = .01). Living alone (η2 = .006), living in a room versus a flat or house (η2 = .008), and being unemployed due to the pandemic (η2 = .008) were related to higher experience of COVID-19 stress. COVID-19 stress and general mental distress were strongly related (r = .53). Both meaningfulness and self-control were negatively associated with general mental distress (r = −.40 and −.36, respectively). They also moderated the relationship between COVID-19 stress and general mental distress: When meaningfulness was high, high COVID-19 stress was related to substantially lower PHQ-4 scores than when meaningfulness was low. The same held for self-control: High scores of self-control were associated with lower PHQ-4 scores especially when COVID-19 stress was high. Crisis of meaning mediated the relationship between COVID-19 stress and PHQ-4. There was a higher likelihood of crises of meaning occurring when COVID-19 stress was high; crisis of meaning, in turn, was associated with general mental distress. Survey group moderated the first path of this mediation, i.e., the relationship between COVID-19 stress and crisis of meaning: High scores of COVID-19 stress were associated more strongly with crisis of meaning in the second survey group (after the lockdown). Self-control moderated the second path, i.e., the relationship between crisis of meaning and PHQ-4: When a crisis of meaning was present, self-control could buffer its effect on general mental distress. Conclusions Also in the present study among German-speaking participants, general mental distress was high. Scores were higher after than during the lockdown, indicating an ongoing destabilization for a significant part of the population. People who saw a meaning in their lives and who were capable of self-control reported substantially less mental distress. Meaningfulness and self-control also served as buffers between COVID-19 stress and general mental distress: When COVID-19 stress was high, the presence of meaningfulness and self-control accounted for lower general mental distress. Moreover, people who suffered strongly from COVID-19 stress were more likely to develop a crisis of meaning which, in turn, was associated with higher general mental distress. This suggests that ongoing anxiety and depression might (also) be based on existential struggles. Again here, self-control buffered the impact of crisis of meaning on general mental health. We conclude from these findings that public health policies can support citizens in coping with large-scale crises by enabling experiences of meaningfulness, e.g., through transparent and reliable modes of communicating goals and necessary intermediate steps. Moreover, health professionals are well advised to invite individuals to confront existential questions and struggles, and to encourage them to exercise self-control. The latter can be boosted by keeping higher-order goals salient—which again is inherently linked to an understanding of their meaning.